Structural and Nutritional Peculiarities Related to Lifespan Differences on Four Lopesia Induced Bivalve-Shaped Galls on the Single Super-Host Mimosa gemmulata - Costa, Elaine C.; Oliveira, Denis C.; Ferreira, Dayse K. L.; Isaias, Rosy M. S. (Frontiers in Plant Science, 2021)
Abstract: Super-host plants are elegant models to evaluate the peculiarities of gall structural and nutritional profiles due to the stimuli of distinct gall inducers in temporal and spatial perspectives. Galls induced by congeneric insects, Lopesia spp. (Diptera, Cecidomyiidae) on the same host plant, Mimosa gemmulata Barneby (Fabaceae) were analyzed to estimate if variations of one or two months in gall lifespans may result in differences over the accumulation of nutritional resources, and their compartmentalization both in cell walls and protoplasm. Mimosa gemmulata hosts four Lopesia-induced galls: the lenticular bivalve-shaped gall (LG) with a 2-month life cycle, the brown lanceolate bivalve-shaped gall (BLG) and the green lanceolate bivalve-shaped gall (GLG) with 3 month-life cycles, and the globoid bivalve-shaped gall (GG) with a 4 month-life cycle. The comparisons among the four Lopesia galls, using anatomical, histometric, histochemical, and immunocytochemical tools, have demonstrated that the longest lifespan of the GG related to its highest increment in structural and nutritional traits compared with the LG, GLG and BLG. The differences among the tissue stratification and cell wall thickness of the galls with the 2-month and the 3-month lifespans were subtle. However, the GG had thicker cell walls and higher stratification of the common storage tissue, schlerenchymatic layers and typical nutritive tissue than the other three gall morphospecies. The higher tissue thickness of the GG was followed by the formation of a bidirectional gradient of carbohydrates in the protoplasm, and the detection of xyloglucans in cell walls. Current data supported the presumption that the longest the lifespan, the highest the impact over the structural and nutritional metabolism of the Lopesia galls associated to M. gemmulata.